ANALISIS PENGARUH KEBIJAKAN IMPOR BERAS TERHADAP PERMINTAAN DALAM NEGERI - Aliya Rizki; Citra Nirmala Pangesti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Rice import policy plays an important role in maintaining national food security in Indonesia, given that rice is a staple commodity for most people. This study aims to analyze the impact of rice import policy from an economic perspective on national food security. The analysis is conducted by analyzing changes in domestic rice supply and demand, price increases, and the influence of international trade policies on the local agricultural sector. In addition, this study also examines the role of rice imports in stabilizing rice prices in the domestic market, especially in the event of crop failures or production disruptions. The results show that rice import policy can provide short-term benefits in the form of price and supply stabilization, but on the other hand, it can weaken the incentives for local farmers to increase production. The implications of this policy should be carefully considered to achieve a balance between short-term food security and long-term sustainability of the agricultural sector. This study recommends the importance of a holistic policy that includes increasing local agricultural productivity, food diversification, and better management of national food reserves.